2015
DOI: 10.2176/nmc.cr.2012-0362
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Siderosis of the Central Nervous System Caused by Hemorrhagic Intraventricular Craniopharyngioma: Case Report and Literature Review

Abstract: Superficial siderosis is a rare condition caused by hemosiderin deposits in the central nervous system (CNS) due to prolonged or recurrent low-grade bleeding into the cerebrospinal fluid (CSF). CNS tumor could be one of the sources of bleeding, both pre- and postoperatively. We report an extremely rare case of superficial siderosis associated with purely third ventricle craniopharyngioma, and review previously reported cases of superficial siderosis associated with CNS tumor. A 69-year-old man presented with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
(55 reference statements)
1
13
0
1
Order By: Relevance
“…Generally, superficial siderosis results from idiopathic bleeding from a vascular abnormality, trauma, brain tumor, or surgery of the central nervous system. 11,[18][19][20][21] Several cases associated with hydrocephalus were also reported, and in such patients, including ours, the impairment of transparenchymal CSF absorption might be associated with nonobstructive hydrocephalus development. 18,22,23 Despite the accumulation of case reports, the relationship between hemorrhage into the CSF and nonobstructive hydrocephalus development has not been well investigated.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Generally, superficial siderosis results from idiopathic bleeding from a vascular abnormality, trauma, brain tumor, or surgery of the central nervous system. 11,[18][19][20][21] Several cases associated with hydrocephalus were also reported, and in such patients, including ours, the impairment of transparenchymal CSF absorption might be associated with nonobstructive hydrocephalus development. 18,22,23 Despite the accumulation of case reports, the relationship between hemorrhage into the CSF and nonobstructive hydrocephalus development has not been well investigated.…”
Section: Discussionsupporting
confidence: 53%
“…We conducted a review of the literature and found several reports of craniopharyngioma associated with hydrocephalus or hemorrhage (►Table 2). 1,5,[8][9][10][11][12] Obstructive hydrocephalus was identified at diagnosis in 49 (45.4%) of 108 patients with craniopharyngioma, but none had nonobstructive hydrocephalus. 12 In our series, obstructive hydrocephalus was identified in 22 patients at diagnosis, and 8 of them (36.4%) required a VP shunt even after tumor removal.…”
Section: Discussionmentioning
confidence: 99%
“…Craniopharyngioma is a rare brain tumor and intratumoral hemorrhage is one of the uncommon manifestations of craniopharyngioma (4). Also, superficial siderosis associated with craniopharyngioma is rarely reported in previous studies (3). We report a rare case superficial siderosis associated with craniopharyngioma with intratumoral hemorrhage.…”
Section: Introductionmentioning
confidence: 78%
“…The mainstay of treatment for superficial siderosis is identification and ablation of the bleeding focus for prevention of progression of symptoms (6). Once symptoms occur, it is difficult to reverse CNS damage caused by hemosiderin deposition (3). Therefore, early diagnosis and timely treatment are important for the better outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation